Exploring the Role of Gratitude in Coping Strategies Among University Students - Maria Batool ,; Jawad Rajab Abbasi,; Samavia Sajid, (Dialogue Social Science Review (DSSR), 2025)
This study examines the relationship between gratitude and coping among university students and how gratitude affects emotional reactivity, regulation, coping with stress and resilience within the academic setting. Quantitatively, the study assessed 150 university students’ levels of gratitude and coping strategies via use of the Gratitude Questionnaire-6 (GQ-6) and Coping Strategies Inventory (CSI). Positive correlations were found between gratitude and problem-focused, emotion-focused and negative coping. Students with elevated levels of gratitude were also more likely to use adaptive coping strategies and less likely to utilize maladaptive ones. Coping strategies of the two sexes were different in nature: while males were found to use problem-focused forms of coping, females had emotion-focused forms of coping. The current findings indicate that when gratitude is fostered, coping skills may be strengthened, stress reduced, and mental health status bettered for undergraduate students. The current results highlight the value of including gratitude interventions in college wellness programs to enhance college students' psychological functioning and stress management.